Antithrombin reduces endotoxin-induced hypotension by enhancing pulmonary sensory neuron activation in rats - Harada, Naoaki; Okajima, Kenji; Isobe, Hirotaka; Uchiba, Mitsuhiro (Thrombosis and Haemostasis, 2006)
We recently demonstrated that activation of the pulmonary sensory neurons plays a critical role in prevention of endotoxininduced shock by releasing calcitonin gene-related peptide (CGRP) in rats. CGRP increased the endothelial production of prostacyclin (PGI2) in the lungs, thereby preventing endotoxininduced shock response by inhibiting tumor necrosis factor-α (TNF-α) production. Since antithrombin (AT) enhances sensory neuron activation, we hypothesized that AT might reduce endotoxin-induced hypotension by enhancing the activation of pulmonary sensory neurons in rats. We examined this possibility using a rat model of endotoxin shock. AT-induced effects including reduction of hypotension (n=5) and inhibition of induction of iNOS (n=4 or 5) and TNF-α (n=5) in the lungs of endotoxin-treated animals were completely reversed by pretreatment with capsazepine (CPZ) (n=4 or 5), a vanilloid receptor antagonist, or CGRP(8–37), a CGRP receptor antagonist (n=4 or 5). AT enhanced endotoxin-induced increases in lung tissue levels of CGRP (n=4), but this effect of AT was not seen in animals pretreated with CPZ (n=4). CGRP produced therapeutic effects (n=5) similar to those induced by AT, and such therapeutic effects were completely abrogated by pretreatment with indomethacin (n=4). AT increased CGRP release from cultured dorsal root ganglion neurons only in the presence of anandamide (n=5),andAT-induced increase in CGRP release was not observed in the presence KT5720, an inhibitor of protein kinase A (n=5). AT markedly increased intracellular levels of cAMP in the presence of anandamide (n=5).These results strongly suggested that AT might reduce endotoxin-induced hypotension in rats by enhancing activation of sensory neurons via activation of protein kinase A.
Keywords: Antithrombin; capsaicin-sensitive sensory neurons; calcitonin gene-related peptide; septic shock; protein kinase A